Validation of two names in Ocellochloa (Poaceae, Panicoideae, Paniceae) - Filgueiras, Tarciso S.; Rodrigues, Rodrigo S. (Phytotaxa, 2012)
The name Ocellochloa soderstromii is validated and Ocellochloa gardneri is proposed to replace the illegitimate name Ocellochloa piauiensis.